# Mobius Band as a Quotient Topology

#### Math Amateur

I am reading Martin Crossley's book, Essential Topology.

I am at present studying Example 5.55 regarding the Mobius Band as a quotient topology.

Example 5.55 Is related to Examples 5.53 and 5.54. So I now present these Examples as follows: I cannot follow the relation $(x,y) \sim (x', y') \Longleftrightarrow \text{ either } (x,y) = (x', y') \text{ or } x = 1 - x' \text{ and } y - y' = \pm 1$

Why do we need $(x,y) = (x', y')$ in the relation? Indeed, why do we need $y - y' = \pm 1$?

Surely all we need is $(x,y) \sim (x', y') \Longleftrightarrow x = 1 - x' \text{ and } y - y' = -1$

Can anyone explain how the relation $(x,y) \sim (x', y') \Longleftrightarrow \text{ either } (x,y) = (x', y') \text{ or } x = 1 - x' \text{ and } y - y' = \pm 1$ actually works to produce the Mobius Band?

Peter

#### Attachments

• 35.7 KB Views: 458
Last edited:

#### Mandelbroth

I cannot follow the relation $(x,y) \sim (x', y') \Longleftrightarrow \text{ either } (x,y) = (x', y') \text{ or } x = 1 - x' \text{ and } y - y' = \pm 1$

Why do we need $(x,y) = (x', y')$ in the relation? Indeed, why do we need $y - y' = \pm 1$?

Surely all we need is $(x,y) \sim (x', y') \Longleftrightarrow x = 1 - x' \text{ and } y - y' = -1$

Can anyone explain how the relation $(x,y) \sim (x', y') \Longleftrightarrow \text{ either } (x,y) = (x', y') \text{ or } x = 1 - x' \text{ and } y - y' = \pm 1$ actually works to produce the Mobius Band?

Peter
Well, it's an equivalence relation, so it has to be reflexive by definition. Thus, if $(x,y)=(x',y')$, then we must have $(x,y)\sim(x',y')$.

Equivalence relations are symmetric as well, so if $(x,y)\sim(x',y')$, then we must have $(x',y')\sim(x,y)$. If $y-y'=1$, then $y'-y=-1$.

• 1 person

### The Physics Forums Way

We Value Quality
• Topics based on mainstream science
• Proper English grammar and spelling
We Value Civility
• Positive and compassionate attitudes
• Patience while debating
We Value Productivity
• Disciplined to remain on-topic
• Recognition of own weaknesses
• Solo and co-op problem solving